Anthropology‐as‐theology: Violent endings and the permanence of new beginnings. Issue 2 (3rd February 2022) - Webster, Joseph
Abstract: This article examines the temporality of dispensationalist imaginings of the apocalypse, with a particular focus on why such imaginings often have an acutely violent character. For the Brethren and for Jehovah's Witnesses, the most convincing signs of the imminent apocalypse are violent ones. By drawing on a mixture of biblical and extra‐biblical images—flames, hail, missiles—dispensationalism creates a semiotic landscape filled with natural, supernatural, and "man‐made" disaster. By analyzing different images of "violent endings" in circulation among the Brethren and Jehovah's Witnesses, this article asks two questions, namely, what are the temporal effects of such violent imaginings, and what imaginings exist on the other side of such violence, after its perpetration? I seek to answer these questions by developing a mode of inquiry I call anthropology‐as‐theology, whereby anthropological analysis deliberately surrenders to theological ideas. I suggest that, when viewed from the perspective of anthropology‐as‐theology, violent dispensationalist visions about the end of the world can provide new perspectives on permanence, which, seen through the lens of revelation, comes to be understood as both novel and eternal. RESUMEN: Este artículo examina la temporalidad de las imaginaciones dispensacionalistas del apocalipsis con un enfoque particular en cómo tales imaginaciones a menudo tienen un carácter extremadamente violento. Para los hermanos y los testigos de Jehová, las señales más convincentes del inminente apocalipsis son violentas. Al basarse en una mezcla de imágenes bíblicas y extrabíblicas –llamas, granizo, misiles– el dispensacionalismo crea un paisaje semiótico colmado de desastre natural, sobrenatural y hecho por humanos. Al analizar imágenes diferentes de "finales violentos" en circulación entre los hermanos y los testigos de Jehová, este artículo hace dos preguntas, a saber, ¿cuáles son los efectos temporales de tales imaginaciones violentas? Y ¿qué imaginaciones existen en el otro lado de tal violencia, después de su perpetración? Busco responder estas preguntas al desarrollar un modo de investigación que llamo antropología‐como‐teología, a través del cual el análisis antropológico deliberadamente se entrega a las ideas teológicas. Sugiero que, cuando visto desde la perspectiva de la antropología‐como‐teología, las visiones dispensacionalistas violentas acerca del final del mundo pueden proveer nuevas perspectivas sobre la permanencia, la cual vista a través del lente de la revelación, llega a ser entendida tanto como novedosa como perpetua. [ apocalipsis, teología, tiempo, milenarismo, cristianismo ] ZUSAMMENFASSUNG: Dieser Artikel untersucht das Zeitverständnis dispensationalistischer Apokalypse‐Vorstellungen, mit Schwerpunkt auf der Frage, warum solchen Vorstellungen oft ein akut gewaltsamer Charakter innewohnt. Für Brüdergemeinden und Zeugen Jehovas gehört Gewalt zu den überzeugendsten Zeichen einer unmittelbar bevorstehenden Apokalypse. In einer Mischung aus biblischen und außerbiblischen Bildern—Flammen, Hagel, Raketen—erschafft ihr Dispensationalismus eine semiotische Landschaft, die mit natürlichen, übernatürlichen und menschengemachten Katastrophen gefüllt ist. Der Artikel analysiert derartige "gewaltsame Enden, " die unter Brüdern und Zeugen Jehovas zirkulieren, und stellt dabei zwei Fragen: was sind die temporalen Effekte solcher gewaltsamen Vorstellungen, und welchen Vorstellungen existieren zur anderen Seite dieser Gewalt, d.h. wenn diese verübt worden ist? Ich versuche diese Fragen mit einer Untersuchungsmethode zu beantworten, die ich Ethnologie‐als‐Theologie nenne, da sich hier Ethnologie absichtlich theologischen Ideen unterwirft. Ich werde aufzeigen, dass gewaltsame dispensationalistische Visionen, wenn sie aus der Perspektive der Ethnologie‐als‐Theologie betrachtet werden, neue Perspektiven auf Permanenz aufscheinen lassen, die wiederum durch die Linse der Offenbarung betrachtet als neu und ewig zugleich verstanden werden kann. [ apokalypse, theologie, zeit, millenarismus, Christentum ]